IMPROVING INSTRUCTIONAL PROCESS IN UTILIZING THE SCHOOL ENVIRONMENT THROUGH THE TEACHERS’ WORK GROUP DISCUSSION AT ELEMENTARY SCHOOLS - Endawinarti; Fefi Yulita (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This research was motivated by the problems found that teachers did not optimally implement the learning process at elementary schools. It was found that many teachers still did not carry out the learning process in accordance with the characteristics of elementary school students, so efforts were needed to improve it. The purpose of this research was to improve the learning process of elementary school teachers which included lesson planning, implementation of learning, and assessment of learning outcomes through KKG discussion activities. The learning process that would be improved was the process using an investigative group type cooperative model. This research was a school action research by adapting the process of implementing Mc Taggart and Kemmist's classroom action research. This research consisted of stages of planning, implementation, observation and reflection. Based on the research conducted, it was found that the teachers’ average skill score in cycle 1 was 66.32 and an average score in cycle 2 was 85.66. This concluded that there was an increase in the teacher learning process skills through KKG activities. The implications of this research was that it could be used as an effort for supervisors to improve teacher skills.